(untitled) (Prilozi za orijentalnu filologiju, 2017)
The aim of this study is to reveal a document written by the people of Bosnia in 1875. This document is a petition and was sent to Ottoman Sadrazam. According to the document, the people of Bosnia had a lot of problems such as the oppression of the officials, bribery, illegal practices and taxes and illegal to regulations. The order was broken. People were poor and had to pay high taxes. The people of Bosnia believed that the Ottoman Sadrazam had to solve their problem.